Simple and accurate quantitative analysis of seven prohibited threshold substances in human urine by liquid chromatography/tandem mass spectrometry in doping control - Lee, Kang Mi; Kim, Ho Jun; Jeong, Eun Sook; Yoo, Hye Hyun; Kwon, Oh Seung; Jin, Changbae; Kim, Dong Hyun; Lee, Jaeick (WILEY-BLACKWELL, 2011)
A simple and accurate liquid chromatography/tandem mass spectrometry (LC/MS/MS) method has been developed and validated for the quantitative determination of ephedrine, pseudoephedrine, methylephedrine, cathine, salbutamol, morphine and epitestosterone in human urine. Urine samples were spiked with internal standard and diluted with acetonitrile. After centrifugation, the supernatants were directly analyzed by LC/MS/MS using the selected reaction monitoring (SRM) mode. The linearity, intra-and inter-day precision, accuracy, limit of detection (LOD) and limit of quantification (LOQ) were evaluated and the method was found to be accurate and reproducible for the quantitation of threshold substances. When the method was applied to the analysis of blind urine samples for the proficiency test, the results were close to the nominal concentrations, within 87.7-106.6% of nominal values, suggesting that the developed methods can be successfully applied to routine doping analyses. Copyright (C) 2011 John Wiley & Sons, Ltd.